1993
DOI: 10.1192/pb.17.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Too high a hurdle? the use of pre-assessment questionnaires in psychotherapy

Abstract: Up to one third of patients referred for psychotherapy fail to attend for their first appointment (O'Loughlin, 1990). Psychotherapy assessments are usually allocated a considerable portion of uninterrupted time, and an unexpected non-attendance wastes significant clinical resources. A variety of strategies have been used to ensure that assessors are not left waiting for a patient who never comes. One method is to send out forms which must be completed and returned before a first appointment date is given. In O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…If completion of the questionnaire was a prerequisite for attending, the figure rises to nineteen patients -a statistically significant result (~2= 11, p=0, df = 1). Two other studies (O'Loughlin1990 and Eynon & Gladwell 1993) have looked at the use of pre-assessment questionnaires: O'Loughlin's (1990) indicated that the team using a questionnaire had fewer non-attendees on the day for a first-assessment appointment -4.8% in the questionnaire group, compared to 22% and 17.7% in control groups; similarly, in Eynon's study (Eynon & Gladwell 1993), figures of 5.6% compared to 13.95%. There are differences in methodology between the present study and these quoted.…”
Section: Analysis Of Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…If completion of the questionnaire was a prerequisite for attending, the figure rises to nineteen patients -a statistically significant result (~2= 11, p=0, df = 1). Two other studies (O'Loughlin1990 and Eynon & Gladwell 1993) have looked at the use of pre-assessment questionnaires: O'Loughlin's (1990) indicated that the team using a questionnaire had fewer non-attendees on the day for a first-assessment appointment -4.8% in the questionnaire group, compared to 22% and 17.7% in control groups; similarly, in Eynon's study (Eynon & Gladwell 1993), figures of 5.6% compared to 13.95%. There are differences in methodology between the present study and these quoted.…”
Section: Analysis Of Resultsmentioning
confidence: 97%
“…Two previous studtes (O 'Loughlin 1990, Eynon & Gladwell 1993) each used psychodynamically formulated pre-assessment questionnaires based upon the one used at the Tavistock Clinic, to look at the difference in attendance rates for first-assessment appointments. They each compared groups of patients who had received a questionnaire to complete, with a control group who had not.…”
Section: The Psychotherapy Questionnairementioning
confidence: 99%
“…Some studies found no significant effect on DNA rates for initial appointments from sending opt-in forms with information leaflets (Ambrose & Ormond, 1996) or from sending a ten-page questionnaire (Markman & Beeney, 1990). On the other hand, Denner and Reeves (1997) and Eynon (1993) both reported that the use of a pre-assessment questionnaire helped reduce DNAs. Various forms of client opt-in, whether by asking clients to send in a return slip indicating their intention to attend (Anderson & White 1994;Green & Giblin 1988), asking them to telephone (Chiesa, 1992) or offering a choice of appointment together with asking for confirmation of attendance (Reid & McIvor 2005), all reduced non-attendance rates.…”
Section: Evidence From Comparable Service Interventions Elsewherementioning
confidence: 99%
“…For example, Markman & Beeney (1990) and Ambrose & Ormond (1996) found no significant effect on DNA rates for initial appointments from sending an opt-in form with an information leaflet, or a ten page questionnaire, respectively. However, Eynon (1993) reported that the use of a psycho dynamically oriented preassessment questionnaire helped reduce DNAs. Various forms of client opt-in, whether by asking client to send in a return slip indicating intention to attend (Anderson & White 1994;Green & Giblin 1988), asking them to telephone (Chiesa, 1992) or offering a choice of appointment together with asking for confirmation of attendance (Reid & McIvor 2005) …”
Section: Dna Ratesmentioning
confidence: 99%